Seed size, number and strategies in annual plants: a comparative functional analysis and synthesis - Hodgson, JG; Marti, GM; Šerá, B; Jones, G; Bogaard, A; Charles, M; Font, X; Ater, M; Taleb, A; Santini, BA; Hmimsa, Y; Palmer, C; et al. (Oxford University Press, 2020)
Background and Aims Plants depend fundamentally on establishment from seed. However, protocols in trait-based ecology currently estimate seed size but not seed number. This can be rectified. For annuals, seed number should simply be a positive function of vegetative biomass and a negative one of seed size.